Physical abilities of patients in the late postoperative period after surgical treatment of complicated diabetic foot syndrome - T V Gracheva (Endocrinology Research Centre, 2011)
Aim. To study physical abilities of patients in the late postoperative period after surgical treatment of complicated diabetic foot syndrome. Materials and methods. This questionnaire study included 116 patients operated in the Department of Purulent Surgery, Sverdlovsk Regional ClinicalHospital No 1, between 01.01.2005 and 31.12.2007. Their physical ability to perform simplest indoor actions was compared with that of 84 DMpatients without diabetic foot syndrome. Results. In less than half of the patients the support function of the lower leg recovered within 1-3 years after discharge due to the presence of nonhealingor new wounds, the necessity of unloading, and the absence of prosthetic treatment. Physical abilities were especially poor after above-the-ankleamputations. The operated patients retained the ability to perform simplest indoor actions comparable with that of control subjects depending on DMduration and BMI. Conclusion. The latter parameter should be corrected as appropriate before the discharge of the patients from the hospital.